The Role of Control and Decision-Making in Online Loan Usage on the Financial Resilience of Bank Employees in Malang City - Noni Oktavianti; Masiyah Kholmi (LP2M IAIN Palopo, 2026)
This study aims to explore how bank employees utilize online loans as part of their financial management strategies and to examine the role of online loans in supporting financial resilience amid increasing economic pressures and rising living costs. This study employed a qualitative approach using a case study research strategy. Data were collected through semi-structured interviews and non-participant observation involving bank employees who had experience using online loan services. The data were analyzed to identify patterns of financial behavior, debt management practices, and adaptive strategies related to financial resilience. The findings reveal that the use of online loans among bank employees cannot be viewed solely as a problematic financial practice. Instead, online loans function as a situational and adaptive financial control mechanism that helps individuals maintain liquidity, manage cash flow, fulfill priority obligations, and preserve economic and social stability. Financial resilience is reflected through continuous adjustments in financial decision-making, selective resource allocation, and the ability to cope with financial stress under dynamic conditions. The study suggests that online loans can serve as a complementary financial instrument when used responsibly and proportionally. For policy and practice, financial institutions and regulators should strengthen financial literacy programs emphasizing debt management and long-term financial planning. Future studies are encouraged to investigate the relationship between online loan usage, financial literacy, and financial resilience across different occupational groups and socioeconomic contexts.